Clinico-epidemiological profile of patients with microbial keratitis in Kashmir valley - Tufela Shafi; Raashid Maqbool Wani; Tasneem Muzaffar; Mehmooda Ashai; Saqib Suraya (International Journal of Medical Research and Review, 2015)
Purpose: This study was undertaken to provide information on the clinico-epidemiological profile of patients clinically suspected with bacterial and fungal keratitis, who were admitted in the Ophthalmology unit of a tertiary center during a 2 year period.Methods: This is a prospective study of all the patients who were admitted in the eye ward of Government Medical College Srinagar (India) between September 2010 and September 2012. 100 patients of bacterial and fungal corneal keratitis without any history of preexisting ocular or systemic disease were included in the study. All patients were assessed, admitted and completely evaluated in hospital and managed accordingly. Corneal ulcer scrapings were taken at presentation, at the Department of Microbiology.Results: Maximum numbers of patients among males (61.90%) were agricultural workers and among females, 81.08% were housewives. It was seen that majority of patients (79%) presented within 1st week of onset of symptoms and among them growth was seen in 64.6%. Growth was seen in 32cases (72.72%) out of 44 cases who gave a history of trauma whereas growth was seen in 36 cases (64.28%) who did not give a clear history of trauma.Conclusion: Bacterial and fungal keratitis in Kashmir is more prevalent in rural areas, with men being more at risk of developing the disease. There is a seasonal variation in the incidence of the disease; higher cases being reported during the harvesting season. Trauma with organic or vegetable matter is a common preceding factor. Microbiological studies should preferably be carried out in all cases.